Comparison of Efficacy and Tolerability of Hylan G-F 20 in Patients with and without Effusions at the Time of Initial Injection - Waddell, Bradford S.; Waddell, W. Hunter; Waddell, David D. (The Journal of Knee Surgery, 2015)
An effusion at the onset of viscosupplementation has been thought to diminish the efficacy and increase adverse event rates. This study compares efficacy of hylan G-F 20 in patients with and without an effusion. Patients with knee osteoarthritis (OA) received three weekly injections of hylan G-F 20. A total of 50 patients with an effusion requiring aspiration were compared with 50 matched patients without an effusion. Outcome measurements included Western Ontario and McMaster's Universities Osteoarthritis index (WOMAC) and visual analog scale (VAS). Patients were followed for 26 weeks. Both effusion and control group VAS was significantly lowered at all time points. WOMAC scores improved (p < 0.025) at all visits in the effusion group except for WOMAC A-1 week 14. Control WOMAC scores also significantly improved at all visits (p < 0.027), except for full WOMAC and WOMAC A-1 at week 1. Neither group experienced an adverse event. Presence of an effusion at onset of viscosupplementation requiring aspiration does not negatively impact efficacy of hylan G-F 20 or increase adverse event rates.
Keywords: viscosupplementation; effusion; knee